РЕЦЕНЗІЯ НА ЕНЦИКЛОПЕДИЧНЕ ВИДАННЯ: ЗАХІДНО-УКРАЇНСЬКА НАРОДНА РЕСПУБЛІКА 1918–1923 - Михайло, Юрій (Літопис Волині, 2023)
РЕЦЕНЗІЯ НА ЕНЦИКЛОПЕДИЧНЕ ВИДАННЯ: ЗАХІДНО-УКРАЇНСЬКА НАРОДНА РЕСПУБЛІКА 1918–1923